Monitoring of bats in key wintering shelters of the Northern Black Sea region (Ukraine) - Mykhailo Drebet (Theriologia Ukrainica, 2022)
Based on the results of winter monitoring of bats conducted in 2020–2022 in key wintering shelters—limestone mines located within the continental part of the Back Sea area and the steppe area of Ukraine (Mykolayiv and Odesa oblasts)—we have recorded 7 species of bats: Myotis daubentonii, M. dasycneme, M. aurascens, M. mystacinus, Plecotus auritus, P. austriacus, and Eptesicus serotinus. Compared to results of monitoring conducted between 2008 and 2011, the number of bats that winter in the mentioned mines has doubled, from 702 to 1421 specimens. One individual of M. aurascens, which was ringed in the mine KVL-K in 2008–2011, was recorded there for the second time. The ring number is VТ 03492, Kyiv, Ukraine. All 5 species of bats were recorded in each of the three monitored caves. The results of the two monitoring sessions appear to be almost identical both by species composition and abundance. The dominating species in the inspected caves and, apparently, generally for winter aggregations of the same type in the region is M. daubentonii. The species’ share in the total sample was 77%. In Kovalsky (KVL-K) and Illyinsky (ILN-K) caves, the co-dominance of two species—M. daubentonii and M. aurascens—was observed (23.3% and 26.8%, respectively). The species M. mystacinus was recorded only in the Kovalivsky caves (9.6%), whereas P. auritus was found only in Novo-Odesky caves (0.1%). The Novo-Odesky mines play a key role in preserving the rare M. dasycneme in Ukraine harbouring the most abundant and widely known accumulation of this species. All investigated caves are particularly important for the preservation of bat populations in the region and their support during critical stages of their life. Granting the Kuyalnik Estuary the status of nature reserve will contribute to the conservation of habitats important for bats. Monitoring of key habitats for conservation of bat species is an important task for the implementation of EUROBATS agreement, which was signed by Ukraine. The obtained data are especially crucial considering the invasion of the Russian Federation to Ukraine since it is unclear when there will be a chance to continue the monitoring of bats in these key winter shelters and what is their current condition.